Secondary Analysis of NCD Risk Factors in Northeast India: Insights from the National Cancer Registry Program - Vemula, Sadanandam; Dhakshanamoorthy, Kalpanapriya (Indian Journal of Community Health, 2024)
Background: The Northeastern Region (NER) of India faces a high cumulative cancer risk, with elevated incidence and mortality rates reported by the National Cancer Registry Program (NCRP). Population-Based Cancer Registries (PBCRs) are crucial in providing essential cancer data for the region. Aims: The study aimed to analyze the distribution of major cancer-associated behavioural and metabolic risk factors at the population level. Its purpose was to support PBCRs in developing a cancer risk factor surveillance program. Methodology: This study adapted the National NCD Monitoring Study (NNMS) cross-sectional, multistage cluster random sampling method, tailoring it to the unique cancer profile of 12 PBCR areas across eight NER states. Results: The survey achieved a 97% response rate. Current tobacco use prevalence (smoke or smokeless) was 45.7% (95% CI: 40.7-50.7), higher in men (61.8%) than women (28.0%). Current alcohol use was 22.3% overall, with men (35.2%) and urban areas (28.7%) showing higher prevalence. Insufficient physical activity was reported by 43.7% in urban areas and 52.5% in women. Conclusion: Insights from the study will aid policymakers in addressing the rising cancer burden through multipronged approaches, including behaviour modification and communication campaigns, to develop locally relevant preventive strategies.